2005
DOI: 10.1016/j.eupc.2005.02.115
|View full text |Cite
|
Sign up to set email alerts
|

Rate-responsive pacing regulated by cardiac haemodynamics

Abstract: The study confirms the reliability of the haemodynamic information derived from TVI and supports its application in the regulation of rate-responsive pacing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Moreover, previous experience demonstrated that the assessment of ventricular volume inferred from TVI data provided reliable information on acute changes in the adrenergic tone, allowing a physiological regulation of the pacing rate. 13–15 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous experience demonstrated that the assessment of ventricular volume inferred from TVI data provided reliable information on acute changes in the adrenergic tone, allowing a physiological regulation of the pacing rate. 13–15 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Biotronik and Medico are using impedance measurements on standard leads; however, the extension of their utility in the clinical practice is very limited. [26][27][28] The major advantage of our system in comparison to the existing systems is that any standard bipolar cardiac lead may be the cardiac contraction sensor without any special device mounted on its body. Furthermore, the sensor does not seem to be affected by factors that influence measurements in impedance sensors such as changes in thoracic anatomy and fluid status, although the signal can be modulated by respiration ( Fig.…”
Section: Advantages Of the Cardiomechanic Sensormentioning
confidence: 99%
“…When inotropic index was used to drive a rate-responsive stimulator (SOPHÒS by Medico, Padova, Italy), the TVI-indicated pacing rate proved a precise replication of the individual sinus rate in patients with physiological chronotropic competence [35]. …”
Section: Rate Responsiveness Haemodynamic Sensorsmentioning
confidence: 99%